2017
DOI: 10.1073/pnas.1617218114
|View full text |Cite
|
Sign up to set email alerts
|

El Niño and the shifting geography of cholera in Africa

Abstract: The El Niño Southern Oscillation (ENSO) and other climate patterns can have profound impacts on the occurrence of infectious diseases ranging from dengue to cholera. In Africa, El Niño conditions are associated with increased rainfall in East Africa and decreased rainfall in southern Africa, West Africa, and parts of the Sahel. Because of the key role of water supplies in cholera transmission, a relationship between El Niño events and cholera incidence is highly plausible, and previous research has shown a lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(66 citation statements)
references
References 42 publications
1
64
1
Order By: Relevance
“…In Kenya, the impacts of El Niño were less severe, with aboveaverage rainfall in OND 2015 leading to improved harvests (FEWS NET KENYA 2016). However, flooding occurred in the west of the country and increased rainfall during this time was associated with an increase in cholera cases (Moore et al 2017).…”
Section: The 2015/16 El Niñomentioning
confidence: 99%
“…In Kenya, the impacts of El Niño were less severe, with aboveaverage rainfall in OND 2015 leading to improved harvests (FEWS NET KENYA 2016). However, flooding occurred in the west of the country and increased rainfall during this time was associated with an increase in cholera cases (Moore et al 2017).…”
Section: The 2015/16 El Niñomentioning
confidence: 99%
“…For West Africa, de Magny et al [83] suggested associations of diarrhoea with El Niño where ENSO, via the so-called Indian Oscillation and associated variations in large scale rainfall and temperature fields, may well influence cholera dynamics and thus diarrhoea. In a consideration of the spatial dynamics of cholera across the African continent, Moore et al [84] demonstrated a clear shift in the annual geographic distribution of cholera in El Niño years, with the burden shifting away from Madagascar and parts of southern, Central, and West Africa, to continental East Africa. They found that during El Niño years for East Africa, there were around 50,000 additional cases of cholera in areas with increased rainfall, along with marked increases in some regions with decreased rainfall.…”
Section: Diarrhoeamentioning
confidence: 99%
“…Briefly, our estimates of cholera incidence were based on suspected and clinically confirmed cholera case reports from 2010 to 2016 obtained from multiple sources, including the World Health Organization (WHO), Médecins Sans Frontières, ProMED, situation reports from ReliefWeb and other websites, several Ministries of Health, and the scientific literature [3,10]. These cholera reports were combined with ecological risk factors such as access to improved drinking water and sanitation and distance to the nearest major body of water to estimate average annual cholera incidence rates at the 20 km x 20 km grid resolution in a Bayesian modeling framework [3,10]. We did not obtain water and sanitation data for Botswana, Djibouti, and Eritrea, and these countries were excluded from our analyses.…”
Section: Epidemiologic and Demographic Data Sourcesmentioning
confidence: 99%
“…Thus, in the rate-logistics optimized strategy, we first ranked countries according to the size of the population residing in high-risk districts, and then targeted vaccines to all high-risk districts in those countries. The highest risk districts were defined as those where cholera incidence exceeded a threshold of 1 case per 1000 persons for at least 100,000 residents or 10% of the population; subsequent tiers of "high-risk districts" employed incidence thresholds of 1 case per 5000, 10,000, and 100,000 persons successively ( Figure S8) [3]. Within each incidence threshold tier, districts were ranked from highest to lowest by estimated cholera incidence rate (hence, rate-logistics).…”
Section: Rate-logistics Optimizedmentioning
confidence: 99%
See 1 more Smart Citation